CONTRIBUTION REGARDING OPTIMIZATION OF TECHNICAL AND TACTICAL TRAINING TO III FEMALE JUNIOR TEAM - Ileana Juravle; Păcuraru Alexandru (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
To reach at high performances, the young handball players which are selected after rigorous criteria must perform an organized training process for a long period of time. The second important factor that leads to performance is considered to be the quality of the training process. This accelerates the process of results obtaining and depends on the teacher training, the upgrade of this training, competitive system, supporting science report, player performance motivation, level of organization reached, the material base and created conditions for training. According to the new Handball developing perspectives on the world level plan, handball players have to be capable of efficiency using of all base technical processes, also an important number of special processes, in term of frequent rate changes and active movement of players in combat with the opponent. Every technical execution must be adjusted with the tactical moment and it have to fit perfectly into the requirements of the overall tactical organization.